Pengaruh Media Pembelajaran Papan Jariber Terhadap Hasil Belajar Matematika - Novita, Ayu; Jayanti, Jayanti; Suryani, Ida (EduTech: Jurnal Ilmu Pendidikan dan Ilmu Sosial, 2022)
This study aims to determine the effect of network Board Learning Media on the Mathematics Learning outcomes of Grade I SD Negeri 1 Bubusan. This type of research uses Quasy Experimental Design, with the form of Pretest-Posttest Control Group Design. The sampel in this study was class 1A which consisted of 22 students as the experimental class and class 1B Which consisted of 18 sudent as the control class. The data analysis technique in this study is the t-test. The results of data analysis calculations obtained the averge value of the experimental class posttest obtained 84,444 and in the control class obtained results of 76,364. Based on the results of hypothesis testing in the posttest value class of the experimental class and the control class posttest using the t-test, a sig , (2-tailed ) value of 0,01 0,05 is obtained so that it is concluded that Ha is accepted. This means that there is an influence of the Jariber Board Learning Media on the Mathamatics Learning Outcomes of Grade I SD Negeri 1 Bubusan